Complete genome sequence analysis of a novel alkane-degrading bacterial strain, Acinetobacter vivianii KJ-1, and its diesel degradation ability - Zhang, Yali; Song, Fanyong; Wang, Jianing; Zhao, Qingqing; Zheng, Liwen; Wang, Zhenjie; Zhang, Xinjian; Gao, Yongchao; Chen, Guanhong; Huang, Yujie (Frontiers in Environmental Science, 2022)
With the increasing demand for diesel in various countries, the ecological pollution caused by the improper use, storage and accidental leakage of diesel needs to be addressed urgently. As an environmentally friendly and cost-effective method, bioremediation mainly is to use various microorganisms to remove pollutants from the environment. Here, the strain KJ-1, obtained through enrichment culture with n- dodecane as the substrate from oil-contaminated soil near the gas station, was identified as Acinetobacter vivianii according to the morphology, biochemistry and molecular biology. The isolate KJ-1 was able to use diesel as the sole carbon source and more than 40% diesel was degraded after 12 days incubation of the strain KJ-1 in MSM. The most suitable diesel concentration and nitrogen source concentration were 4,140 mg/L and 350-700 mg/L for the diesel degradation and the bacterial growth. The optimal initial pH and temperature for strain KJ-1 growth and diesel degradation were 6.5-8.0 and 30-35°C, respectively. To investigate the diesel degrading mechanisms of this strain, the complete genome was sequenced and annotated. The complete genome consists of one chromosome with a total length 3,927,757 base pairs and a G+C content of 41.5%. The genes related to the two-component regulatory system and alkane degrading were analyzed. In addition, two putative alkane monooxygenases were further analyzed, and the protein sequences were characterized and compared with other AlkBs in Acinetobacter spp. downloaded from NCBI. From the results, it is demonstrated that A. vivianii KJ-1 may be particularly useful for future bioremediation for diesel polluted soil.